Preferential Solvation of the Antioxidant Agent Daidzein in some Aqueous Co-Solvent Mixtures according to IKBI and QLQC Methods (2023)
The preferential solvation parameters by ethanol (EtOH) or propylene glycol (PG) of daidzein were derived from their solution thermodynamic properties by means of the inverse Kirkwood-Buff integrals and the quasi-latticequasi-chemical (QLQC) methods.